2022
DOI: 10.1038/s41392-022-01245-y
|View full text |Cite
|
Sign up to set email alerts
|

Protein acylation: mechanisms, biological functions and therapeutic targets

Abstract: Metabolic reprogramming is involved in the pathogenesis of not only cancers but also neurodegenerative diseases, cardiovascular diseases, and infectious diseases. With the progress of metabonomics and proteomics, metabolites have been found to affect protein acylations through providing acyl groups or changing the activities of acyltransferases or deacylases. Reciprocally, protein acylation is involved in key cellular processes relevant to physiology and diseases, such as protein stability, protein subcellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 415 publications
(501 reference statements)
1
51
0
Order By: Relevance
“…For example, SIRT2 was reported as an ‘eraser’ to remove acetyl, crotonyl, methacrylyl, and benzoyl marks on histones as well as non‐histone proteins (Bao et al., 2014; Bhaskar et al., 2020; Delaney et al., 2021; Huang et al., 2018; Ntorla & Burgoyne, 2021; Serrano et al., 2013; Yi et al., 2021). Some studies have found that metabolic enzymes are involved in the pathogenesis of diseases by targeting more than one modification (Shang et al., 2022). Therefore, profiling dynamic changes of different modifications and elucidating how they compete with regulatory enzymes for downstream functionality is important to understand the underlying mechanisms of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SIRT2 was reported as an ‘eraser’ to remove acetyl, crotonyl, methacrylyl, and benzoyl marks on histones as well as non‐histone proteins (Bao et al., 2014; Bhaskar et al., 2020; Delaney et al., 2021; Huang et al., 2018; Ntorla & Burgoyne, 2021; Serrano et al., 2013; Yi et al., 2021). Some studies have found that metabolic enzymes are involved in the pathogenesis of diseases by targeting more than one modification (Shang et al., 2022). Therefore, profiling dynamic changes of different modifications and elucidating how they compete with regulatory enzymes for downstream functionality is important to understand the underlying mechanisms of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…CoA also mediates the covalent transfer of other acyl moieties to proteins for the dynamic modulation of their activity. Several acyl-CoA metabolites, including succinyl-CoA, propionyl-CoA, crotonyl-CoA, and palmitoyl-CoA, can be covalently attached to the side chains of lysines of proteins in different cellular compartments [ 36 ]. As for acetylation, the acylation of proteins has a role in regulating cellular processes, such as gene expression and chromatin accessibility, metabolic regulation, subcellular targeting, protein–membrane interactions, protein stability, and folding [ 37 ].…”
Section: Coenzyme a Homeostasis And Functionsmentioning
confidence: 99%
“…Phosphorylation primarily modifies serine residues followed by threonine and tyrosine residues, in eukaryotes, but can also be present on histidine and aspartic acid residues in prokaryotes, and these modifications can lead to strong structural rearrangements . Changes in PTM profiles are associated with dysregulated biological mechanisms and diseases, such as metabolism disorder, inflammation, neurodegenerative diseases, cancer, and cardiovascular disease. Highly specific kinase inhibitors, for example, provide popular therapeutic intervention mechanisms for diseases. …”
Section: Introductionmentioning
confidence: 99%